Faktor-faktor yang mempengaruhi kinerja karyawan di Kota Pekanbaru - Putri, Sonia Sischa Eka (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2021)
This study aims to examine : The influence of good corporate governance, organizational culture, motivation competence, leadership style and utilization of information technology on the employee performance. The study was conducted at companies in the Pekanbaru City. This research was conducted on 87 people who work in the 20 companies in the city of Pekanbaru. The results showed that: good corporate governance has influence on employee performance where in its implementation it will have a positive impact on the organization, organizational culture has a role in organizational growth that will support performance, motivation of each individual will encourage the achievement of organizational targets through good employee performance, competencies possessed by human resources also become Important factors in achieving organizational goals, leadership style and the use of information technology also has an influence in employee performance in companies of Pekanbaru City.